+0  
 
0
23
2
avatar

Enter all the solutions to (x - 2)(25 - x^2) = -50.

 
 Jun 7, 2021
 #1
avatar+122 
+1

x = 0, 1+√26, 1−√26

 
 Jun 7, 2021
 #2
avatar+119772 
+2

(x - 2) ( 25 - x^2)  =  -50

 

25x  - 50  - x^3  + 2x^2  = -50          add 50  to  both sides

 

-x^3  + 2x^2  +  25x  =  0               multiply through by -1

 

x^3  -  2x^2  - 25x  =  0                 factor

 

x  ( x^2  - 2x   - 25)  =  0

 

x = 0            and        x^2   -  2x   -  25   =  0

                                 complete the square on x

                                   x^2  - 2x + 1  =  25 + 1

                                     (x  - 1)^2  =   26               take both roots

                                     x - 1  = sqrt 26               x - 1  =  - sqrt 26

                                     x  = 1 + sqrt 26               x  =  1  - sqrt 26

                                 

 

 

cool cool cool

 
 Jun 7, 2021

12 Online Users

avatar
avatar